Corneal and conjunctival foreign bodies caused by a firecracker at RSUD Panembahan Senopati Bantul: Poster Presentation - Case Report - General practitioner - Layli nur arniati; Sekar Harry Satyawati (Majalah Oftalmologi Indonesia, 2023)
Introduction : The majority of firecracker ocular injuries occur under the age of 20 years. The most common injuries were lid injuries, corneal abrasions, and superficial foreign bodies. Case Illustration : An 11-year-old patient came to the Emergency Room with redness, pain, and decreased vision in both eyes. The patient was hit by a firecracker an hour before. The visual acuity in the right and left eyes were 0.2 and 0.8. There were several red spots on his face, body and multiple foreign bodies on the superficial cornea and conjunctiva of both eyes. Irrigation with Ringer Lactate solution was done immediately followed by extraction of multiple foreign bodies under local anesthesia on the next day. Medical therapy consists of topical antibiotics, Atropine Sulphate and artificial tears were given. Discussion : Firecracker ocular injury has many symptoms, such as redness (100%), pain (97%), watering (86%), reduced vision (77%), and foreign body sensation (12%). In this case, we found all the clinical signs. The management of ocular foreign bodies caused by firecrackers could be conservative. This includes irrigation, topical antibiotics, and removal of ocular foreign bodies which should be done within 24 hours after the injury. In this case, we did all the treatment. Due to an incooperative patient, removal of corneal and conjunctival foreign bodies was done in 24 hours for the right eye and 48 hours for the left eye. Conclusion : Firecracker ocular injury can have serious consequences for ocular morbidity and visual acuity. Prompt diagnosis and meticulous management can prevent devastating sequelae.